Improving students learning motivation through mobile learning - Alfiana Monika Sari; Heru Nurcahyo (University of Muhammadiyah Malang, 2018)
One of the obstacles to achieving learning objectives is the low motivation of student learning. This study aimed to determine the improvement of students learning motivation through mobile learning. This pre-experimental study consisted of 35 students of XIPA1 as a subject while the population is all the students of State Senior High School 1 of Banguntapan – Yogyakarta. The sampling technique used purposive sampling. Data collection used questionnaires were given before and after learning. Data analysis used paired t-test and N-gain score to see the effectiveness of mobile learning in increasing students learning motivation. The results showed that by using the mobile learning had a significant effect on students' learning motivation with a significance value (α) of 0.00 <0.05 while the N-gain score was included in the medium category, which was 0.64. The conclusions from this study indicate that mobile learning can increase learning motivation.